The Impact of the Smolensk Air Crash on the Attributionof Personality Traits to Political Parties - Gorbaniuk, Oleg (Current Problems of Psychiatry, 2010)
The aim of the study was to check whether and in what way the tragic death of the Polish political elite near Smolensk on 10 April 2010 affected the perception of politicians and political parties in Poland. A comparison was made between survey results concerning personality traits attributed to political parties two weeks before and two weeks after the crash of the presidential plane. During both stages of the study, 140 students described six Polish political parties using a list of personality descriptors. The results of the study showed that the experience of tragic events, the period of mourning, the mobilisation of society, and the insight that these afforded into the more human side of politicians changed the perception of parties on the Polish political scene. The most extensive of the changes observed were the increase of the parties’ perceived openness for cooperation and the attribution of fewer asocial traits to them. The change concerned the major political parties, regardless of how many members each of them actually lost in the crash.